The Expansion of Legal Application of Military Law on Legal Subjects that Equated with the Military Based on Republic of Indonesia Law - Ilman Hadi; Irwan Triadi; Parluhutan Sagala (Transpublika Publisher, 2025)
A nation as an entity needs a way to maintain its existence as best as possible through its own capabilities through a national military formed to carry out national defense duties. Generally, the term